Renewable Energy and CO2 Emissions in Top Natural Resource Rents Depending Countries: The Role of Governance - Szetela, Beata; Majewska, Agnieszka; Jamroz, Paweł; Djalilov, Bekhzod; Salahodjaev, Raufhon (Frontiers in Energy Research, 2022)
This study analyzes the relationship between renewable energy and CO2 emissions in top natural resource depending countries over the period 2000–2015. An important contribution of this study is to assess the role of governance. The Ordinary Least Squares Fixed effects Generalized Least Squares methods and two-step GMM estimators are used for panel data. The empirical results show that renewable energy has significant negative impact on per capita CO2 emissions. The estimates show that 1 percentage point increase in renewable energy consumption leads to 1.25% decrease in CO2 emissions per capita. We also find that renewable energy consumption decreases CO2 emissions faster in countries with higher rule of law and voice and accountability. gross domestic product per capita has inverted U-shaped relationship with CO2 emissions.